2012
DOI: 10.2527/jas.2011-4630
|View full text |Cite
|
Sign up to set email alerts
|

LACTATION BIOLOGY SYMPOSIUM: Effects of photoperiod on mammary gland development and lactation1

Abstract: Photoperiod, or the daily sequence of light and dark, has dramatic effects on many physiological systems across animal species. Light patterns alter melatonin secretion profiles and, subsequently, the release profiles and circulating concentrations of several hormones that influence a variety of physiological responses. Although the impact of photoperiod on reproductive processes is perhaps the most common example, it is often the seasonal aspects of ovulation and anestrus that are considered. However, in catt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 37 publications
1
36
0
1
Order By: Relevance
“…; Dahl et al. ). In response to this, plasma prolactin concentrations decline but prolactin receptor expression increases in many tissues, including the liver, mammary gland and lymphocytes (Auchtung et al.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Dahl et al. ). In response to this, plasma prolactin concentrations decline but prolactin receptor expression increases in many tissues, including the liver, mammary gland and lymphocytes (Auchtung et al.…”
Section: Discussionmentioning
confidence: 97%
“…Photoperiod changes in cattle include low concentrations of melatonin observed under light conditions and their marked increase under conditions of darkness (Dahl et al. ). The effects of these changes on the reproductive performance of cattle seem limited (Hansen et al.…”
Section: Discussionmentioning
confidence: 99%
“…photoperiod), plane of nutrition and growth rate during the prepubertal period can each impinge on the development of the mammary gland in a manner that will determine milk yields during subsequent lactations (Robinson et al 1999;Dahl et al 2012). The curvilinear nature of the relationship between weight gain during the rearing period and mammary gland development is such that reductions of around 10% in milk yields have been reported, particularly in firstlactation dairy heifers that were either under-or overfed during the peripubertal period.…”
Section: Prepubertal Development and Subsequent Milk Yieldsmentioning
confidence: 99%
“…Recent studies have shown its protective effect on viability of LPSstimulated bovine mammary epithelial cells and mastitis, and improved quality of milk by reducing somatic cells count (Shao et al, 2015;Yang et al, 2017;Yu et al, 2017). Studies have shown that administration of exogenous melatonin during long days or artificial RESEARCH ARTICLE stimulation of short days affect milk protein and casein contents in sheep and cows (Dahl et al, 2012;Molik et al, 2012). However, no reports are available regarding protein contents in buffalo.…”
Section: Introductionmentioning
confidence: 99%